Epidemiology of soccer injuries in Korea women national team for 5 years - Joo, C.-H. (Journal of Exercise Rehabilitation, 2022)
The purpose of this study was to analyze the characteristics of injuries in female national soccer players. The injuries data were recorded by Korea Football Association medical staff using the Daily Medical Report provided by the Asian Football Confederation during a total 21 training camps and friendly and official matches from January 2014 to December 2018. A total of 483 players in the national team training camps and matches participated in the study, of which 377 players experienced more than one injury. Sports injuries accounted for 89% of the total 1,019 injuries; general diseases accounted for the remaining 11%. The number of injuries per 1,000 exposure hours was higher in matches than in training sessions. Most injuries that occurred during training and matches involved the lower extremities (79%). The most common injury diagnosed during training and matches was muscle rigidity (45%), followed by contusions/hematomas/bruises (22%) and sprain (15%). The largest proportions of injuries in terms of absence from soccer play were minimal injury (67%), followed by mild (29%), moderate (3.5%), and severe (1%). As conclusion, the characteristics of injuries during training sessions and matches were different. Rehabilitation and injury prevention programs need to developed for female soccer players to improve the players` performance.